Conceptualizations of Development from the Cultural Perspective: Progresses and Challenges in a Diverse World (Revista LIDER, 2020)
All countries aspire to achieve the long awaited development, but what isdevelopment? This study offers a look at the different approaches of development, an analysis of some theoretical and practical efforts made to try to integrate ethnic diversity and culture under the logic of human development, and finally some possible challenges to be faced by this research line.